The influence of political changes in Germany after the First World War on the composition of provincial parliaments in Silesia - Kruszewski, Tomasz (The Opole Studies in Administration and Law, 2020)
The author presents the rules of suffrage that were binding in Zweites Reich (The Second Reich), that is the German Empire, during elections to provincial self-government in Prussia and then compares them with the new election law implemented in the Weimar Republic (Weimarer Republik). In this way it is possible to establish the degree of potential changes that influenced the personal composition of provincial parliaments. Upon the analysis of the given lists of deputies it clearly follows that a revolution took place in Germany in November 1918: up to that time the Members of Parliament had represented the elites of the Second Reich, recruiting from, among others, aristocrats, the nobility, state administration officials, municipal elites, high mayors, mayors, other officials of municipal councils and industrialist elites. The majority of these people in Weimar Republic were replaced by party activists, which resulted from the new electoral law.